Comparison of Preoperative Administration of Rectal Diclofenac and Acetaminophen for Reducing Post Operative Pain in Septorhinoplastic Surgeries - E Allahyry; SH Tarig; AH Chohedri; ZS Fattahi; F Talei (Armaghane Danesh Bimonthly Journal, 2006)
ABSTRACT: